PENGARUH PENERAPAN SISTEM MANAJEMEN SUMBER DAYA PERUSAHAAN DALAM MENINGKATKAN KINERJA MANAJEMEN RANTAI PASOK PT. PEGAUNIHAN TECHNOLOGY INDONESIA - Qadr, Rizni Aulia; Alex, Alex; Joycelin, Joycelin; Liu, Michelle Selvia; Marliana, Selvia Eka; Shelvi, Shelvi (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
Information technology has an important role in business processes, one of whichis the implementation of ERP (Enterprise Resource Planning) which is softwareintended to help organizations manage and create effective use of resources byproducing integrated solutions. ERP provides beneficial implications in businessprocesses. One of them is the company's supply chain process. This study aims toanalyze how the ERP (Enterprise Resource Planning) system is implemented andits influence on business operations in every company department, especially in thesupply chain management department of the company chosen as the object ofanalysis, namely PT. Pegaunihan Technology Indonesia. The methodology used inthis study is qualitative research methods, especially qualitative descriptions andcase studies. Based on the results of the analysis presented, it can be concluded thatthe implementation of ERP at PT. Pegaunihan Technology Indonesia, especially inthe supply chain management department, creates responsiveness, effectivenessand efficiency that is integrated into its processes and performance.Keywords: ERP, Company Performance, Effectiveness and Efficiency,Information Integration, Supply Chain Management,